Health Services Research: A Review for the Interventional Radiologist - Marchak, Katherine; Malavia, Mira; Trivedi, Premal S. (Seminars in Interventional Radiology, 2023)
Health services research (HSR) is a multidisciplinary field which studies access to drivers of health care service utilization, the quality and cost of services, and their outcomes on groups of patients. Since its foundations in the 1960s, there has been a large focus on HSR and using large data sets to study real-world care. Because interventional radiology (IR) is a dynamic field with foundations in innovation, research often focuses on small-scale projects. This review will discuss HSR including data sources, focus areas, methodologies, limitations, and opportunities for future directions in IR.
Keywords: health services research; interventional radiology; big data; outcomes; population health